Design of highway bridges an LRFD approach - Barker, R. M. (Richard M.) (Wiley, 2013)
"Here is the updated edition of Wiley's premier reference on the engineering design and analysis of short and medium-span bridges using the Load and Resistance Factor Design (LRFD) methodology. The text has been thoroughly updated throughout to conform with changes made in the latest edition of the AASHTO LRFD Bridge Design Specifications. With content reorganized into smaller and more succinct chapters, coverage also features computer modeling, calibration of service limit states, rigid method system analysis, the green aspects of recycled steel, and concrete shear"--